Mesenchymal stem cell therapy in a rat model of birth-trauma injury: functional improvements and biodistribution. Issue 2 (February 2016) - Sadeghi, Zhina; Isariyawongse, Justin; Kavran, Michael; Izgi, Kenan; Marini, Gabriela; Molter, Joseph; Daneshgari, Firouz; Flask, Chris; Caplan, Arnold; Hijaz, Adonis
Abstract Introduction and hypothesis We evaluated the potential role of human mesenchymal stem cells (hMSCs) in improvement of urinary continence following birth-trauma injury. Methods Human MSCs were injected periurethrally or systemically into rats immediately after vaginal distention (VD) (n  = 90). Control groups were non-VD (uninjured/untreated, n  = 15), local or systemic saline (injection/control, n  = 90), and dermofibroblast (cell therapy/control, n  = 90). Leak-point pressure (LPP) was measured 4, 10, and 14 days later. Urethras were morphometrically evaluated. In another sets of VD and non-VD rats, the fate of periurethrally injected hMSC, biodistribution, and in vivo viability was studied using human Alu genomic repeat staining, PKH26 labeling, and luciferase-expression labeling, respectively. Results Saline- and dermofibroblast-treated control rats demonstrated lower LPP than non-VD controls at days 4 and 14 (P  < 0.01). LPP after systemic hMSC and periurethral hMSC treatment were comparable with non-VD controls at 4, 10, and 14 days (P  > 0.05). Local saline controls demonstrated extensive urethral tissue bleeding. The connective tissue area/urethral section area proportion and vascular density were higher in the local hMSC- versus the saline-treated group at 4 and 14 days, respectively. No positive Alu-stained nuclei were observed in urethras at 4, 10, and 14 days. PKH26-labelled cells were found in all urethras at 2 and 24 h. Bioluminescence study showed increased luciferase expression from day 0 to 1 following hMSC injection. Conclusions Human MSCs restored the continence mechanism with an immediate and sustained effect in the VD model, while saline and dermofibroblast therapy did not. Human MSCs remained at the site of periurethral injection for <7 days. We hypothesize that periurethral hMSC treatment improves vascular, connective tissue, and hemorrhage status of urethral tissues after acute VD injury.